The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1016/s0896-6273(00)80493-6
|View full text |Cite
|
Sign up to set email alerts
|

Subunit Composition, Protein Interactions, and Structures of the Mammalian Brain sec6/8 Complex and Septin Filaments

Abstract: Both the sec6/8 complex and septin filaments have been implicated in directing vesicles and proteins to sites of active membrane addition in yeast. The rat brain sec6/8 complex coimmunoprecipitates with a filament composed of four mammalian septins, suggesting an interaction between these complexes. One of the septins, CDC10, displays broad subcellular and tissue distributions and is found in postmitotic neurons as well as dividing cells. Electron microscopic studies showed that the purified rat brain septins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
299
0
10

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 323 publications
(332 citation statements)
references
References 56 publications
(25 reference statements)
14
299
0
10
Order By: Relevance
“…These observations indicate that septins might contribute to the process of cell division through a more general role in either directing or enhancing the efficiency and specificity of membrane remodeling [21]. In agreement with a role in membrane synthesis, septins in animal cells associate with components of the secretory apparatus, such as the exocyst complex and a SNARE protein (syntaxin) [22,23]. Moreover, although in many higher cell types septins localize to the site of cytokinesis [2,3] and the metaphase plate [24], a subset of septins is expressed highly in post-mitotic tissues such as brain [25], which indicates that the contribution of septins to cell function is not confined to either cytokinesis or chromosome dynamics.…”
Section: Septin Functionsmentioning
confidence: 85%
“…These observations indicate that septins might contribute to the process of cell division through a more general role in either directing or enhancing the efficiency and specificity of membrane remodeling [21]. In agreement with a role in membrane synthesis, septins in animal cells associate with components of the secretory apparatus, such as the exocyst complex and a SNARE protein (syntaxin) [22,23]. Moreover, although in many higher cell types septins localize to the site of cytokinesis [2,3] and the metaphase plate [24], a subset of septins is expressed highly in post-mitotic tissues such as brain [25], which indicates that the contribution of septins to cell function is not confined to either cytokinesis or chromosome dynamics.…”
Section: Septin Functionsmentioning
confidence: 85%
“…Although there is no known mammalian homolog for Bud4p, a counterpart exists for each septin and exocyst subunit. The mammalian exocyst [Sec6-Sec8 (EXOC3-EXOC4) complex] has been co-purified and immunoprecipitated with septins (Hsu et al, 1996;Hsu et al, 1998;Hsu et al, 1999); like its yeast counterpart, it was found to influence polarized vesicle delivery (Hsu et al, 1999). Mammalian septins were individually identified and implicated in cytokinesis, exocytosis, vesicle-targeting and membrane dynamics (Spiliotis and Nelson, 2006;Beites et al, 1999;Trimble, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In each species examined to date, there are two or more septins that form heterooligomeric complexes to perform their specific functions. Purified septins from yeast, Drosophila, Xenopus, and mammalian cells form filaments of 7-9 nm diameter and of variable length (Field et al, 1996;Frazier et al, 1998;Hsu et al, 1998;Kinoshita et al, 2002;Mendoza et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For example, considerable evidence suggests that the septins are involved in one or more steps of vesicle trafficking in mammalian cells (Hsu et al, 1998;Beites et al, 1999;Kartmann and Roth, 2001;Dent et al, 2002). In yeast, the septins play roles in bud-site selection, the spatial organization of cell-wall deposition, and the "morphogenesis checkpoint" that couples cell-cycle progression to progress in bud formation Sanders and Herskowitz, 1996;DeMarini et al, 1997;Barral et al, 1999;Shulewitz et al, 1999;Longtine et al, 2000;Schenkman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation